Functionalization of cellulose nanocrystals with γ-MPS and its effect on the adhesive behavior of acrylic pressure sensitive adhesives. (1st August 2019) - Yu, Qingqing; Yang, Weijun; Wang, Qianqian; Dong, Weifu; Du, Mingliang; Ma, Piming
Highlights: Functionalization of CNC with vinyl groups was achieved through grafting γ-MPS. Acrylic PSA with CNC was synthesized by in-situ semi-continuous seeding emulsion polymerization. Superior adhesive properties of fCNC/acrylic PSA were obtained. Abstract: In this work, functionalized cellulose nanocrystal (fCNC) was obtained by the grafting of 3-methacryloxypropyltrimethoxysilane coupling agent (γ-MPS) onto CNC. Then acrylic pressure sensitive adhesive (PSA) incorporated with various contents of CNC or fCNC was successfully synthesized by an in-situ emulsion polymerization, and the effects of CNC or fCNC on the sol molecular weight, latex properties, thermal properties, viscoelastic properties, and adhesive performance of the acrylic PSA were investigated. The results illustrated a coinstantaneous improvement of tack, shear strength and peel strength with increasing the loading of both CNC and fCNC. Interestingly, fCNC showed much more improvement than CNC on adhesive performance of acrylic PSA. The fCNC-1/acrylic PSA showed tack of 27#, shear strength of 70 h, and peel strength of 13.4 N/25mm, which were 12.5%, 4%, and 106% higher than those of CNC-1/acrylic PSA and 35%, 100%, and 163% higher than those of neat acrylic PSA, respectively. The superior adhesive performance of the fCNC/acrylic PSA films was supposed to be attributed to better compatibility and dispersion of fCNC in the acrylic copolymer. Thus, this work presents a feasible strategy for utilization of CNC in adhesives and coatings.